(3GdJMOjGJ h GdaQU h GdBaGbs ((3YeGf(B:s (3ecJHI GdeLJeY(B,s, 2010)
(3GdJMOjGJ h GdaQU GdJj JhGLg GdGOGA GdJShjbj , GdGfXeI GdHjFjI ddCYeGd (B: (3CTcGd LOjOI ddJYGhf h GdJfGaS MGdI GdJcfhdhLjGJ GdLOjOI , GdJLGQI GdGjdeJQhfjI (B: (3Jbjje GdLghO GdJShjbjI , eTcdGJ GdJcjja GdHjFj h GfYcGSGJgG Ydi feh GdTQcGJ GdGLfHjI , GdeZGfe h GdeZGQe GdGbJUGOjI aj GJaGbjI GdTQGcI GdCQOfjI GdChQhHjI , OhQ GdHfhc GdGSdGejI aj GdJfejI , GdeUGQa GdGSdGejI h OhQgG aj GdJfejI GdGbJUGOjI , GdeJZjQGJ GdGbJUGOjI GdOhdjI h CKQgG Ydi GdJcGed GdGbJUGOj GdYQHj , GdJcJdGJ GdGbJUGOjI h GdJLGQI GdOhdjI h GdJcGed GdGbJUGOj GdYQHj , GdJcJdGJ GdGbJUGOjI GdOhdjI h JaYjd GdJYGhf GdGbJUGOj GdYQHj , LhOI GdNOeGJ GdGjdjcJQhfjI defXeGJ GdGYeGd aj Xd GdYhdeI , GdbGFO GdeHOY cejRI JfGaSjI defXeGJ GdGYeGd GdOhdjI , GOGQI GdeYQaI h JcfhdhLjG GdeYdheGJ h OhQgG aj JMbjb bjeI YGdjI dCYeGd efXeGJ GdGYeGd GdOhdjI , OQGSI JMdjdjI ddCNWGA GdeDOjI Gdi SbhW bQGQGJ ebOQj GdVQjHI aj eQMdI GdGYJQGV h GdGSJFfGa(B.s
(3eQGLY U(B.559s
Keywords: (3EOGQI GdGYeGds; (3efXeGJs